An Assessment of the Enabling Environment for Climate-Resilient Community-Managed WASH Systems in Nepal - Singh, Resham Jung; Ibrahim, Nurazim; Pandey, Vishnu Prasad (NPRC Journal of Multidisciplinary Research, 2026)
Background: Climate change exacerbates hydro-meteorological hazards that impact water availability, infrastructure, and water quality in rural Nepal, where Water Users and Sanitation Committees (WUSCs) are responsible for the operation and management of most of the water supply systems, in which local governments are the primary service delivery authority as well as regulatory body. Objective: This research aims to evaluate the current status of the enabling environment for climate-resilient and community-managed WASH services in Nepal by analyzing existing policies and readiness gaps in six interrelated pillars: governance, policy and legal operationalization, institutional and technical capacity, financing systems, coordination and information systems, and equity and inclusion. Methods: A qualitative policy analysis was performed through a systematic document analysis of 16 national policy documents related to WASH and climate change. Thematic analysis, qualitative content analysis, discourse analysis, and comparative gap analysis were employed through an analytical framework of six interrelated pillars with an adequacy scale (Strong, Moderate, Limited, Weak) for policy readiness assessment. Findings: The enabling environment has moderate adequacy in terms of governance and policy operationalization, but limited adequacy in terms of institutional capacity, financial support, and coordination mechanisms, and limited to moderate adequacy in terms of equity and inclusion. Although there is a clear mandate for decentralization and a clear intention for climate policies, there are still important gaps: climate resilience is not integrated into binding service standards; municipal human resources and technical support for WUSCs are inadequate; financial support prioritizes capital spending over life-cycle and shock-responsive approaches; climate information is inadequately integrated into WASH operational guidelines; and equity measures lack implementation tools. Conclusion: The policy intention for climate-resilient WASH in Nepal is strong, but operationalization is fragmentary among the interrelated pillars. Without filling these systemic gaps, adaptation will continue to be a set of reactive coping measures, rather than institutionalized, preventive, and sustainable resilience actions. Implementation: The research identified an integrated climate-resilient framework to institutionalize resilience through: municipal service monitoring with standardized criteria; WASH units; climate risk screening in technical approval processes; provincial technical support pools; separate O&M and resilience budgets; simplified access to climate finance; cross-sectoral coordination tools; and enhanced equity criteria with clear grievance handling.